Thoracoscopic intraoperative esophageal close technique for long‐gap esophageal atresia. Issue 1 (2nd May 2021) - Ieiri, Satoshi; Kai, Hiroki; Hirose, Ryuichiro
Abstract: Long‐gap esophageal atresia (EA) remains a challenging operative procedure. Several techniques have been reported to resolve the problem of distance between the proximal and distal esophagus. We report a thoracoscopic intraoperative esophageal close technique for long‐gap EA. A female neonate was born at 39 weeks of gestation with long‐gap EA (five vertebrae). The patient underwent thoracoscopic esophageal anastomosis after esophageal elongation. Careful dissection of the proximal and distal esophagus was performed; however, the distance between them was still long. Extra‐thoracic traction sutures were placed at the upper esophagus. Then, a Neraton catheter was inserted trans‐orally and the upper esophagus was pushed and opened. An internal traction suture was placed between the Neraton catheter and lower esophagus. The gap between the proximal and distal esophagus could be approximated by pulling the Neraton catheter. Esophageal anastomosis was performed successfully. Our thoracoscopic intraoperative esophageal close technique was simple and useful.